Hubungan Dukungan Orang Tua dengan Motivasi Belajar Penjas Siswa Kelas Tinggi - Muliadi Muliadi; Firdaus Firdaus; Annida Us Salamah Adz Dzikru (Universtas Negeri Makassar, 2022)
The problem in this study is the lack of parental support so that it can affect the motivation to learn Physical Education. This study is a quantitative study with a correlation approach that aims to determine the relationship between parental support and physical education learning motivation. The results showed that obtained rx = 0.547 then the relationship between the two variables was classified at the level of relationship in the